Study of the Physical and Chemical Properties of the Euphrates River Water in the City of Hit - Alwan, Arwa Soud (American Journal of Biomedicine and Pharmacy, 2025)
The study includes a comparison of the Euphrates River’s physical and chemical characteristics in the city of Hit between October 2024 and April 2025 with the normative standards for drinking water in Iraq and elsewhere. Turbidity, electrical conductivity, total dissolved salts, pH, total hardness, and total basicity were all measured as part of the study, along with the concentrations of various positive and negative ions. The findings of all physical and chemical testing were confirmed to be within the acceptable limits for drinking water after being compared to the standard requirements. Low rainfall, high temperatures, and a small percentage of Iraq’s water coming from the source nation were the causes of the high values of dissolved salts, total hardness, and sulfates in November. The high concentration of suspended particles in the research was also attributed to the breakdown of aquatic vegetation and the occurrence of flash floods during rainstorms, which cause some soil to be eroded into the river.